Rare Cause of Soft Tissue Infection: Shewanella algae - Yılık, Ezgi; Akgül, Ayşe Hümeyra; Gençeli, Mustafa; Akcan, Özge Metin; Kan, Seda Nur Arazi; Doğan, Metin (Journal of Pediatric Infectious Diseases, 2024)
Shewanella algae is a common microorganism in nature, but a rare pathogen in humans. It is a causative agent of skin and soft tissue infections, especially in patients with skin ulcers or trauma. S. algae can enter the body through the eyes, ears, gastrointestinal tract, or respiratory tract. Immunocompromised individuals are at increased risk of developing bacteremia and sepsis from the infection. This report presents a case of posttraumatic soft tissue infection caused by S. algae in an 18-year-old male after swimming in the sea. The bacteria were cultured from the wound site.
Keywords: Shewanella algae; soft tissue infections; abscess